Examination of the eating behaviours and depression states of the university students who stay at home during the coronavirus pandemic in terms of different variables - Serin, Emre; Koc, Mustafa Can (Progress in Nutrition, 2020)
Study Objective: This study aims to examine the eating behaviors and depression states of the university students who stay at home during the coronavirus pandemic in terms of different variables. Methods: The study group consists of 1064 participants in total (440 men and 624 women). In addition to the personal information form, The Dutch eating behavior questionnaire (DEBQ), and the CES-Depression scale (CES-D) were used in the study. The normality test of the data was checked with the Shapiro-Wilk Test. The Mann Whitney-U test was used to compare continuous data between two independent groups, and the Kruskal Wallis-H test was used to compare continuous data between more than two independent groups. In addition, Spearman Correlation Analysis was used to determine the relationship between dependent variables. Results: As a result, a significant difference was found in all variables including age, gender, self-isolation, regular physical activity at home during the Covid-19, and before the Covid-19 Outbreak. In addition, in the correlation between eating behaviour scale sub-dimension scores and depression scale scores, no significant relationship was found between depression and external eating. Conclusion: It can be said that nutrition and mental health are as important issues as viruses in the process of (covid-19) pandemic.